Functioning of the Folk Poetic Symbols in the Poetry of Ukrainian Symbolism (Case Study of V. Pachovskyi's Creativity) (Linguostylistic Studies, 2019)
The article describes an investigation of the linguistic and symbolic code of poetry of the Ukrainian symbolism of the late nineteenth and early twentieth centuries using the works of V. Pachovsky, who was one of the representatives of that poetic movement. The case study is based on the cognitive approach to the analysis of stylistic units. The cognitive meaning of the folk poetic symbols in the discourse of the poetry of symbolism of the specified period is considered on the basis of the regularity of the symbolic imagery functioning in the poet’s writings. The study has revealed the specificity of the individual and authorial symbolic renewal of symbols. The frame-slot organization of folk poetic concepts, their role in verbalizing the author's linguistic picture of the world are in the focus of the analysis. The approach used by cognitive stylistics is based on the theories that explain the choice of the linguistic means through cognitive structures and processes underlying their formation The approach used by cognitive stylistics is based on theories that explain the choice of linguistic means through cognitive structures and processes underlying their formation. The main methods of cognition are used in this work, in particular the metaphorical analysis and the methods of transformation and distributive analysis. These methods enable modeling of the main folk poetic concepts in the works of V. Pachovskyi, a poet-symbolist. The research material comprises the poetic segments that contain the above mentioned ethnocultural concepts, as well as their frame organization. The emphasis is laid on the basic concepts related to the folk poetic symbols, for example, a concept of a bird (dove, swallowtail, cuckoo, cranes, peacock, hawk, raven, eagle, swan, nightingale), a concept of a snake, concepts of plants and flowers (rose, lily, cornflowers), etc.The conducted research allows to draw a conclusion that the folk poetic symbols in the discourse of the symbolists of the late nineteenth and early twentieth century function not only as the means of intensification and deepening the imagery or expression of folklore details, but also as cognitive presentation of the individual author's picture of the world. The analyzed concepts convey the ethno-cultural information, since Ukrainian symbolism has grown on a national basis. Symbolists sought to combine common cultural heritage and national worldview. Therefore, in the process of verbalizing traditional concepts, V. Paсhovsky employed new senses which characterize the author's picture of the world. Decoding the conceptual content of folk poetic symbols enables and contribute to deeper understanding of the texts of the symbolism age. Key words: idiostyle, linguistic picture of the world, conceptual picture of the world, cognitive stylistics, symbol, folk poetic symbol, concept, frame, slot. SourcesPachovskyi, Vasyl. Zibrani tvory. 2 vols. Filadelfiia–Niu-York–Toronto : Obiednannia ukrainskykh pysmennykiv «Slovo», 1984. ReferencesBoldyrev, Nikolaj. “Koncept i znachenie slova”. Metodologicheskie problemy kognitivnoj lingvistiki, edited by I. A. Sternin. Voronezh: VGU, 2001, pp. 25–36.Bulashev, Heorhii. Ukrainskyi narod u svoikh lehendakh, relihiinykh pohliadakh ta viruvanniakh.  Kyiv : Firma “Dovira”, 1992.Vezhbickaja, Anna. Jazyk. Kul'tura. Poznanie. Moskva : Russkie slovari, 1997.Vinogradov, Viktor. Stilistika. Teorija pojeticheskoj rechi. Pojetika. Moskva, 1963.Voitovych, Valerii. Sokil-Rod: lehendy ta mify starodavnikh ukraintsiv. Rivne, 1997.Voropai, Oleksa. Zvychai nashoho narodu: etnohrafichnyi narys. Kyiv : Oberih, 1991.Hnatiuk, Volodymyr. Narys ukrainskoi mifolohii. Lviv, 2000.Yermolenko, Svitlana. Folklor i literaturna mova. Kyiv : Naukova dumka, 1987.Zhabotinskaja, Svetlana. “Konceptual'nyj analiz: tipy frejmov”. Cherkasy University Bulletin: Philological Sciences, iss. 11, 1999, pp. 3–20Zhaivoronok, Vitalii. Znaky ukrainskoi etnokultury. Kyiv : Dovira, 2006.Zhaivoronok, Vitalii. “Problema kontseptualnoi kartyny svitu ta movnoho yii vidobrazhennia”. Kul'tura narodov Prichernomor'ja, no 32, 2002, pp. 51–3.Kerlot, Huan. Slovar' simvolov. Moskva : REFL-book, 1994.Kononenko, Vitalii. Kontsepty ukrainskoho dyskursu. Kyiv-Ivano-Frankivsk : Plai, 2004.Kononenko, Vitalii. Mova u konteksti kultury. Kyiv – Ivano-Frankivsk, 2008.Kostomarov, Mykola. “Neskol'ko slov o slavjano-russkoj mifologii v jazycheskom periode, preimushhestvenno v svjazi s narodnoju pojezieju”. Slovianska mifolohiia: vybrani pratsi z folklorystyky y literaturoznavstva. Kyiv : Lybid, 1994, pp. 257–79.Kostomarov, Mykola. “Ob istoricheskom znachenii russkoj narodnoj pojezii”. Slovianska mifolohiia: vybrani pratsi z folklorystyky y literaturoznavstva. Kyiv : Lybid, 1994, pp. 44–201.Kostomarov, Mykola. “Slavianskaia mifolohiia”. Slovianska mifolohiia: vybrani pratsi z folklorystyky y literaturoznavstva. Kyiv : Lybid, 1994, pp. 201–57.Kubrjakova, E. S., Dem'jankov, V. Z., Pankrac, Ju. G., and Luzina, L. G. Kratkij slovar' kognitivnyh terminov. Moskva, 1997.Levchenko, Olena. Doslidzhennia verbalnykh symvoliv u linhvokulturolohichnomu aspekti. dspace.nbuv.gov.ua/ bitstream/handle/ 123456789/73947/07-Levchenko.pdf? sequence=1Levchenko, Olena. Frazeolohichna symvolika: linhvokulturolohichnyi aspekt. Lviv, 2005.Losev, Aleksej. Znak. Simvol. Mif. Moskva : Izdatel'stvo MGU, 1982.Losev, Aleksej. Problema simvola i realisticheskoe iskusstvo. Moskva : Iskusstvo, 1976.Lun'kova, Larisa. Kognitivnaja stilistika: obrabotka i dekodirovanie hudozhestvennogo teksta. Moskva : RUSAJNS, 2018.Maslova, Valentina. Lingvokul'turologija. Moskva : Izdatel'skij centr «Akademija», 2001.Potebnja, Aleksandr. “O nekotoryh simvolah v slavjanskoj narodnoj pojezii”. Simvol i mif v narodnoj kul'ture. Moskva : Labirint, 2000, pp. 5–91.Rizhko, Ruslana. “The Folklorisms Cognitive Filling in the Poetic Picture of the World at the End of the ХХ – the beginning of the XXI Centuries”. Zhytomyr Ivan Franko State University Journal, iss. 58, 2011, pp. 186–192.Selivanova, Olena. Suchasna linhvistyka: napriamy ta problemy. Poltava: Dovkillia-K, 2008.Simovych, Oksana. Poetychna symvolika ukrainskoi narodnoi tvorchosti: linhvistychnyi aspekt. Lviv, 1999.Slipushko, Oksana. Davnoukrainskyi bestiarii: henezys i systema. Kyiv: Dnipro, 2001.Jung, Carl. Chelovek i ego simvoly. Moskva : Serebrjannye niti, 1997.